Two Wheeler Aero Braking System - V B Babu, T; Ram Kumar, R; Saravanan, G; Vishnu Annamalai, V; Giridharan, L (International Journal of Engineering and Technology, 2018)
The most commonly used transport system in our country is two wheeler transport system. In that there are varieties of vehicle with vast engine specifications which generate more power. As well as there are many advanced braking system which is invented to reduce or stop the vehicle Even though, the accident rate is increasing day by day. One of the main reasons for the accident is the stopping distance of the vehicle.This project is mainly based on reducing the stopping distance of the vehicle and balancing the vehicle at emergency conditions. We achieve that by creating a drag force against the thrust force. This drag is created with the help of wings which is fixed on both sides of the vehicle. The wings are operated by rack and pinion mechanism which was connected to the starter motor. The starter motor is activated by the driver by means of switch. By implementing our project in commercial vehicle we can reduce the rate of accidents occurring in our day to day life.Â